If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x = 53 Solving -1x = 53 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-1'. x = -53 Simplifying x = -53
| y=x^7-2x^2+3 | | 7x^2+51x+14= | | y^4+12y^3+35y^2=0 | | 9+9+9(-2)+7= | | 6[x-(5x-6)]=8-9x | | 13x=1/5 | | 6(k+2)=3(2k-5) | | 47=4x+10+7x-7 | | 15=5(3x-10)-5x | | -6.8(4x+6)-1.7(3x-5)= | | 16y=112 | | 3(80x-9x)=x-96 | | 8a-6a+3=7 | | 16=12-x | | 3m-9n=2 | | 2g-5=6 | | 2z-3=4z-1 | | 6a^2+12a-48=0 | | 36=3x+2+6x+7 | | (2x+5)8=72 | | -36-52= | | 4.5-1.5(6m+2)=3 | | 7+3*4-1=39 | | 3y-4(y+2)=2(3y-2) | | -1-10(10r+6)= | | -3n-5n=8 | | 5x^2+5y=45 | | 3z-9=3 | | -2x+6=16 | | 7p=35 | | (x-5)(x-6)=6 | | 4x-7=7x-5 |